Taxonomy of the Proisotoma complex. VI. Mobile forms of Proisotoma s.str. with the description of a new species from East Siberia (Collembola: Isotomidae) - Potapov, Mikhail; Bogomolov, Maxim (Zootaxa, 2016)
Phenotypic dimorphism of four species of the genus Proisotoma s.str. is described. The modified specimens are characterized by protruding corneas of eyes, stronger pigmentation, enlarged and more chitinized furca, and extension of clavate tenent hairs in the distal part of the tibiotarsi. The characteristics of the modified specimens indicate higher mobile activity. Both sexes are affected by the dimorphism, with the "mobile" forms mostly co-occuring during the cold season with normal specimens. Proisotoma dualis sp. nov. is described from Buryat Republic.